Diophantus method of determining of freguency damages as a result of implementations information security threat - Безштанько, Виталій Михайлович; Цуркан, Василь Васильович (Ukrainian Information Security Research Journal, 2013)
Implementation of information security management systems based on risk assessments is a promising approach of ensuring the confidentiality, integrity and availability of state information resources. Risk assessment is expressed as a combination of frequency of damage occurrence as a result of the threat and its absolute value. Therefore the choice of the method for determining of its assessment leads to the choice of the method of determining the frequency of damage occurrence. Using traditional approaches to solving this problem is limited to the complexity of the statistics accumulation of damage. To overcome this limitation developed a method of determining the relative frequency of a linear inhomogeneous Diophantine equation in positive integers. It allows through adjusting acceptable values the amount of damage and acceptable risk values to get guaranteed solutions as model risk assessments. Making a decision on the necessity of their treatment in the management of information systems security is possible basing on received results.